MiR‐15a‐5p regulates expression of multiple proteins in the megakaryocyte GPVI signaling pathway. (25th February 2019) - Basak, Indranil; Bhatlekar, Seema; Manne, Bhanu K.; Stoller, Micelle; Hugo, Sarah; Kong, X.; Ma, L.; Rondina, Matthew T.; Weyrich, Andrew S.; Edelstein, Leonard C.; Bray, Paul F.
Abstract : Essentials The action of microRNAs (miRs) in human megakaryocyte signaling is largely unknown. Cord blood‐derived human megakaryocytes (MKs) were used to test the function of candidate miRs. miR‐15a‐5p negatively regulated MK GPVI‐mediated αIIbβ3 activation and α‐granule release. miR‐15a‐5p acts as a potential "master‐miR" regulating genes in the MK GPVI signaling pathway. Summary: Background: Megakaryocytes (MKs) invest their progeny platelets with proteins and RNAs. MicroRNAs (miRs), which inhibit mRNA translation into protein, are abundantly expressed in MKs and platelets. Although platelet miRs have been associated with platelet reactivity and disease, there is a paucity of information on the function of miRs in human MKs. Objective: To identify MK miRs that regulate the GPVI signaling pathway in the MK‐platelet lineage. Methods: Candidate miRs associated with GPVI‐mediated platelet aggregation were tested for functionality in cultured MKs derived from cord blood. Results: An unbiased, transcriptome‐wide screen in 154 healthy donors identified platelet miR‐15a‐5p as significantly negatively associated with CRP‐induced platelet aggregation. Platelet agonist dose‐response curves demonstrated activation of αIIbβ3 in suspensions of cord blood‐derived cultured MKs. Overexpression and knockdown of miR‐15a‐5p in these MKs reduced and enhanced, respectively, CRP‐induced αIIbβ3 activation but did not alter thrombin or ADP stimulation. FYN, SRGN, FCER1G, MYLK . and PRKCQ, genes involved in GPVI signaling, were identified as miR‐15a‐5p targets and were inhibited or de‐repressed in MKs with miR‐15a‐5p overexpression or inhibition, respectively. Lentiviral overexpression of miR‐15a‐5p also inhibited GPVI‐FcRγ‐mediated phosphorylation of Syk and PLCγ2, GPVI downstream signaling molecules, but effects of miR‐15a‐5p on αIIbβ3 activation did not extend to other ITAM‐signaling receptors (FcγRIIa and CLEC‐2). Conclusion: Cord blood‐derived MKs are a useful human system for studying the functional effects of candidate platelet genes. miR‐15a‐5p is a potential "master‐miR" for specifically regulating GPVI‐mediated MK‐platelet signaling. Targeting miR‐15a‐5p may have therapeutic potential in hemostasis and thrombosis.